PENGARUH KINERJA KEUANGAN TERHADAP TINGKAT PENGEMBALIAN SAHAM PERUSAHAAN - Islamay, Sherina Anggie; Jimena Arilyn, Erika (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research was conducted to determine the impact of liquidity, activity, debt, profitability, and market ratio on stock return. The population used in this research was wholesale firms listed on Bursa Efek Indonesia from 2014 to 2020. This research used purposive sampling method to gather 8 firms as a sample, also used causal research to determine the impact of independent variables on dependent variable and Multiple Linier Regression to analyze the data. Result of the research concluded that debt and market ratio impact the stock return. The use of debt is proven could increase the return of firm’s stock, and also for market ratio characterized by an increase in market price of firm’s stock or a decrease of the amount of common stock equity could increase the stock return of the firms.